Incidence of Hyponatremia During a Continuous 246-km Ultramarathon Running Race - Seal, Adam D.; Anastasiou, Costas A.; Skenderi, Katerina P.; Echegaray, Marcos; Yiannakouris, Nikos; Tsekouras, Yiannis E.; Matalas, Antonia L.; Yannakoulia, Mary; Pechlivani, Fani; Kavouras, Stavros A. (Frontiers in Nutrition, 2019)
Purpose: The purpose of this observational study was to examine the incidence of exercise-associated hyponatremia (EAH) in a 246-km continuous ultra-marathon. Methods: Over 2 years, 63 male finishers of the annual Spartathlon ultra-marathon foot race from Athens to Sparta, Greece were included in the data analysis. A blood sample was drawn from an antecubital vein the day before the race as well as within 15 min post-race and analyzed for sodium concentration. During the second year of data collection, blood was also drawn at the 93-km checkpoint (n = 29). Height and weight were measured pre and post-race. Results: Mean race time of all subjects was 33 ± 3 h with a range of 23.5 and 36.0 h. Of the 63 finishers recruited, nine began the race with values indicative of mild hyponatremia. Seven runners were classified as hyponatremic at the 93-km checkpoint, three of whom had sodium levels of severe hyponatremia. After the race, 41 total finishers (65%) developed either mild (n = 27, 43%) or severe hyponatremia (n = 14, 22%). Mean change in bodyweight percentage and serum sodium from pre-race to post-race was −3.6 ± 2.7% (−2.5 ± 1.9 kg) and −6.6 ± 5.6 mmol·L−1, respectively. Pre-race serum sodium level was not a significant predictor of post-race serum sodium levels (β = 0.08, R2 = 0.07, P = 0.698), however, there was a significant negative association between change in bodyweight percentage and post-race serum sodium concentration (β = −0.79, R2 = 0.29, P = 0.011). Conclusion: The incidence of EAH of 52 and 65%, when excluding or including these individuals with pre-race hyponatremia, was the highest reported in current literature.